Peran sistem audit dalam lembaga keuangan syariah di Indonesia - Khoirun, Dwi Sasi (Maliki Interdisciplinary Journal, 2026)
The audit system plays a strategic role in ensuring the integrity and compliance of Islamic financial institutions (LKS) with sharia principles. This study aims to analyze the functions, types, role of the Sharia Supervisory Board (DPS), challenges, and efforts to strengthen the Islamic audit system in Indonesia. The research method used is a descriptive qualitative approach through literature review from various recent sources. The findings show that the audit system is not only a financial control tool but also plays a vital role in ensuring LKS operations remain aligned with sharia values. Islamic audits involve various types including internal, external, and sharia compliance audits. The DPS plays a central role in audit implementation, although it still faces challenges such as limited human resources, lack of standardization, and weak technological integration. Therefore, strengthening the sharia audit system must be carried out through auditor training, regulatory enhancement, and collaboration between regulators and LKS. These efforts are essential to support the sustainable, accountable, and sound growth of Islamic finance in Indonesia.